Mezi praxí a teorií v učitelském vzdělávání: na okraj českého překladu knihy F. A. J. Korthagena et al. Between practice and theory in teacher education: notes on the Czech translation of Korthagen et al.'s book. - Najvar Petr; Janík Tomáš; Slavík Jan; Píšová Michaela (Czech Pedagogical Society, 2012)
This theoretical paper follows the publication of the Czech translation of the book by F. A. J. Korthagen et al. Linking practice and theory: The pedagogy of realistic teacher education. The paper consists of two parts. In the first part, the key (leading) ideas of Korthagen's approach are introduced; the text is descriptive without the ambition to provide a critical analysis. Such analysis is the topic of the second part of the text. The authors revisit some of the ideas of Korthagen's approach, analyse them and discuss them in a wider context of some newer approaches. They focus on three problem areas: (1) The nature of the relationship between practice and theory - underestimating Theory with capital T? (2) The importance of reflection in teachers' professional development - deemphasising content? (3) Supporting professional learning - a limited view on supervision? Towards the end of the paper, the authors discuss how the presented ideas could inspire the practice of teacher education in the Czech Republic.